The effect of infection with the entomopathogenic fungus Conidiobolus coronatus (Entomopthorales) on eighteen cytokine-like proteins in Galleria mellonella (Lepidoptera) larvae - Wrońska, Anna Katarzyna; Kaczmarek, Agata; Sobich, Justyna; Boguś, Mieczysława Irena (Frontiers in Immunology, 2024)
Background In response to the replace mammal research models with insects in preliminary immunological studies, interest has grown in invertebrate defense systems. The immunological response is regulated by cytokines; however, while their role in mammals is well understood, little is known of their function in insects. A suitable target for studies into insect immunology is Galleria mellonella (Lepidoptera), the wax moth: a common host for human fungal and bacterial pathogens. G. mellonella is also a perfect subject for studies into the presence of cytokine-like proteins. Specific Objectives The main goal of present research was detection in insect immunocompetent cells the 18 mammalian cytokines (IL-1α, IL-1β, IL-2, IL-3, IL-6, IL-7, IL-8, IL-12, IL-13, IL-15, IL-17, IL-19, IFN-γ, TNF-α, TNF-β, GM-CSF, M-CSF, G-CSF), which play important role in immunological response and indication how their level change after fungal infection. Methodology The changes of cytokine-like proteins level were detected in hemocytes taken from G. mellonella larvae infected with entomopathogenic fungus, C. coronatus. The presence of cytokine-proteins was confirmed with using fluorescence microscopy (in cultured hemocytes) and flow cytometry (in freshly collected hemolymph). The ELISA test was used to detect changes in concentration of examined cytokine-like proteins. Results Our findings indicated the presence of eighteen cytokine-like molecules in G. mellonella hemocytes during infection with C. coronatus. The hemocytes taken from infected larvae demonstrated higher fluorescence intensity for six cytokine-like proteins (GM-CSF, M-CSF, IL-3, IL-15, IL-1β and IL-19) compared to untreated controls. ELISA test indicated significantly higher IL-3 and IL-15. M-CSF, IL-1α and IL-19 concentration in the hemolymph after fungal infection, and significantly lower TNF-β and G-CSF. Conclusions Our findings confirm that the selected cytokine-like molecules are present in insect hemocytes and that their concentrations change after fungal infection, which might suggest that they play a role in the anti-fungal immunological response.